Ideological and worldview features of Mikhas’ Mashara creativity on the pages of «Chryścijanskaja dumka» magazine: textological aspect - Yurkoits, Dzmitry A. (Journal of the Belarusian State University. Philology, 2025)
The creative heritage of the Western Belarusian poet Mikhas’ Mashara, published on the pages of the religious magazine «Chryścijanskaja dumka», is considered. It is proved that in order to identify the ideological and worldview guidelines of the author’s work, one cannot limit oneself to the cultural-historical method of research, it is necessary to use auxiliary textual analysis. Ideological changes in poems subsequently republished in Soviet times have been identified, which suggests the difficulty of objectively considering the poet’s work while ignoring original publications. It is concluded that the work of Mikhas’ Mashara is characterised not only by the breadth and courage of thinking, features of imaginism, but also by existential motives that are alien to the tendentious Soviet poetry of the 1930s.
Keywords: Western Belarusian poetry; ideological and worldview guidelines; textological analysis; periodicals; Mikhas’ Mashara; magazine «Chryścijanskaja dumka»; the image of the future